Balconies' visual preferences: The case of residential apartments in Tehran, Iran. - Paria Akbari; Seyed-Abbas Yazdanfar; Saeid Norouzian-Maleki; Seyed-Bagher Hosseini (PLoS ONE, 2025)
Balcony as a border between internal and external plays a crucial role in determining the quality of the apartments. The current condition of apartment balconies in Tehran, indicates that balconies have been gradually been forgotten due to their non-functional features for users. In architecture, space quality is measured by user preferences and can serve as a guide for designers in future designs. The objective of the present study was to identify the dominant physical characteristics of balconies in Tehran and improve people's visual preference from both outside and inside viewpoints. Photographing, Delphi technique and collecting public questionnaire were used to do the research, and quantitative data were gathered through administering questionnaires. Valid responses were gathered, then the collected data were analyzed using SPSS. According to the results, there is a significant difference between the two categories of pleasant and unpleasant. In addition, the characteristics of desirable images from the outside and inside are not always the same. From the outside view of the balcony, the area is the most effective parameter, which in pleasant images was between 50% and 75% of the façade area. Fully solid and completely fences parapet, were preferred from the outside view, while from the user's point of view, the space from the inside of the balcony with a completely fences parapet was unpleasant and a completely solid or a combination of a solid and fences was preferred.